Substorm topology in the ionosphere and magnetosphere during a flux rope event in the magnetotail - Amm, O.; Nakamura, R.; Frey, H. U.; Ogawa, Y.; Kubyshkina, M.; Balogh, A.; Rème, H. (Annales Geophysicae, 2006)
On 13 August 2002, at ~23:00 UT, about 10 min after a substorm intensification, Cluster observes a flux rope in the central magnetotail, followed by a localised fast flow event about oneminute later. Associated with the flux rope event, a traveling compression region (TCR) is seen by those Cluster spacecraft which reside in the lobe. In the conjugate ionospheric region in Northern Scandinavia, the MIRACLE network observes the ionospheric equivalent currents, and the electron densities and electric fields are measured by the EISCAT radar along a meridional scanning profile. Further, the auroral evolution is observed with the Wideband Imaging Camera (WIC) on the IMAGE satellite. We compare in detail the substorm evolution as observed in the ionosphere and in the magnetosphere, and examine whether topological correspondences to the flux rope event exist in the ionospheric signatures. The large-scale mapping of both the location and the direction of the flux rope to the ionosphere shows an excellent correspondence to a lens-shaped region of an auroral emission minimum. This region is bracketed by an auroral region equatorward of it which was preexisting to the substorm intensification, and a substorm-related auroral region poleward of it. It is characterised by reduced ionospheric conductances with respect to its environment, and downward field-aligned current (FAC) observed both in the magnetosphere and in the ionosphere. As determined from the ionospheric data, this downward FAC area is moving eastward with a speed of ~2 km s-1, in good agreement with the mapped plasma bulk velocity measured at the Cluster satellite closest to that area. Further southwestward to this leading downward FAC area, a trailing upward FAC area is observed that moves eastward with the same speed. The direction of the ionospheric electric field permits a current closure between these two FAC areas through the ionosphere. We speculate that these FAC areas may correspond to the ends of the flux rope in its symmetry direction.